System Integration Integrated Digital Accounting and Electronic Tax Reporting in Increase Tax Compliance and MSME Performance in Palembang City - Fransisca Dyah Anggraini; Arif Aliyanto; Andrew Gunawan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The rapid advancement of digital transformation has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt digital technologies to improve financial management and strengthen tax compliance. However, previous studies have reported inconsistent findings regarding the extent to which Integrated Digital Accounting Systems and Electronic Tax Reporting contribute to MSME performance, particularly through the mechanism of tax compliance. This study aims to examine the effects of Integrated Digital Accounting Systems and Electronic Tax Reporting on MSME Performance, with Tax Compliance serving as a mediating variable. A quantitative research approach was employed using primary data collected from 120 MSME owners in Palembang City, Indonesia, selected through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that both Integrated Digital Accounting Systems and Electronic Tax Reporting have positive and significant effects on Tax Compliance. Tax Compliance also has a positive and significant effect on MSME Performance. Furthermore, Integrated Digital Accounting Systems directly enhance MSME Performance, whereas Electronic Tax Reporting does not have a significant direct effect. Mediation analysis reveals that Tax Compliance significantly mediates the relationship between Electronic Tax Reporting and MSME Performance but does not mediate the relationship between Integrated Digital Accounting Systems and MSME Performance. These findings suggest that digital accounting systems create strategic value by directly improving financial management and business performance, whereas the effectiveness of electronic tax reporting depends on its ability to strengthen tax compliance. This study contributes to the literature on digital transformation, accounting information systems, and taxation by providing empirical evidence on the strategic role of tax compliance in enhancing MSME performance. The findings also offer practical implications for policymakers, tax authorities, technology providers, and MSME owners in promoting digital transformation to improve business.